2021
DOI: 10.1016/j.celrep.2020.108637
|View full text |Cite
|
Sign up to set email alerts
|

Snd3 controls nucleus-vacuole junctions in response to glucose signaling

Abstract: Highlights d Snd3 is essential for the formation of nucleus-vacuole junctions d Snd3 links structural changes of nucleus-vacuole junctions to glucose availability d Glucose exhaustion triggers the targeting of Snd3 to the junctions d Snd3 promotes contact site expansion downstream of PKA and Snf1 signaling

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 62 publications
0
40
0
Order By: Relevance
“…Upon cultivation on standard minimal media containing 2% glucose, cells exit cell cycle and enter quiescence as soon as glucose is exhausted [37]. To identify a setup in which cells enter stationary phase due to gradual depletion of phosphate instead of glucose but are still supplemented with sufficient phosphate to allow normal exponential growth, we monitored cellular growth across a range of phosphate concentrations.…”
Section: Phosphate Restriction Induces Longevitymentioning
confidence: 99%
“…Upon cultivation on standard minimal media containing 2% glucose, cells exit cell cycle and enter quiescence as soon as glucose is exhausted [37]. To identify a setup in which cells enter stationary phase due to gradual depletion of phosphate instead of glucose but are still supplemented with sufficient phosphate to allow normal exponential growth, we monitored cellular growth across a range of phosphate concentrations.…”
Section: Phosphate Restriction Induces Longevitymentioning
confidence: 99%
“…Whichever the case, the process will imply a deep remodeling of the contacts between the nuclear and vacuolar membranes. It is therefore possible that proteins implicated in vacuole-nucleus membranes hyper-tethering, such as Nvj1, Mdm1 and Snd3, are important players (5,8,9,15). Their study will be a key entry point to dissect the mechanism of vacuole ingression in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The tether between these two membranes is actively maintained by the proteins Vac8 and Nvj1, present in the vacuolar and outer nuclear membranes, respectively (7). Helped by additional factors, such as Snd3 (8), the NVJ expands "zipper-wise" during nutritional stress, such as glucose and aminoacid shortage, and upon Target Of Rapamycin Complex (TORC) inhibition (9). This increase in the contact surface can serve to send esterified lipids for storage within Lipid Droplets (9), to increase the flux of metabolites through the mevalonate pathway (5) or to recycle non-essential nuclear components (10).…”
Section: Introductionmentioning
confidence: 99%
“…One examples of this is Mdm10, which forms part of the sorting and assembly machinery (SAM) complex of the mitochondrial outer membrane (Ellenrieder et al, 2016;Meisinger et al, 2004) and of the ERMES complex, a stable tether between the endoplasmic reticulum and the mitochondria (Kornmann et al, 2009). Another example is the protein Snd3, which is a component of the SND machinery, responsible for targeting proteins to the endoplasmic reticulum (Aviram et al, 2016), and was recently shown to be a part of the contact site formed between the vacuole and the nuclear endoplasmic reticulum (Tosal-Castano et al, 2021). In both of these cases, as for Vps39, the proteins engage in these moonlighting functions in MCSs, independently of the other subunits of the complex of which they form part in their other functions.…”
Section: Dynamic Formation Of the Vps41-vps3-class C Intermediate Complexmentioning
confidence: 99%
“…MCS are increasingly recognized as regulated by different metabolic pathways. For example, the nuclear-vacuolar junction changes its size in response to glucose availability (Hariri et al, 2017;Tosal-Castano et al, 2021), and the vacuole-peroxisome MCSs expands in conditions of peroxisomes proliferation (Wu et al, 2019). Whether these moonlighting proteins regulate cross-regulation of membrane contact sites with other cellular processes like for example vesicular transport (Vps39) or protein biogenesis (Tom40, Snd3, Mdm10) is an appealing model that needs to be addressed in future research.…”
Section: Dynamic Formation Of the Vps41-vps3-class C Intermediate Complexmentioning
confidence: 99%